Bronchial responsiveness and symptoms in 5-6 year old children: a comparison of a direct and indirect challenge. Issue 4 (April 1995) - Wilson, N M; Bridge, P; Silverman, M
Abstract : BACKGROUND–The level of bronchial responsiveness in those with definite asthma correlates with disease severity and markers of airway inflammation. However, in population studies no clear distinction between normal and abnormal is found. Since the outcome of wheeze in early childhood is very variable, a marker of underlying airway inflammation would be of practical value. A stimulus acting indirectly may be more appropriate than one acting directly on smooth muscle. In this study the airway response to a direct (methacholine) and indirect (hypertonic saline) challenge have been compared in 5-6 year old children with past or present wheeze to see if symptom patterns or severity could be distinguished by either test. METHODS–Forty children with a wide spectrum of wheeze were monitored for a six month period after which their pattern and severity of symptoms were graded. Hypertonic saline and methacholine challenges were then performed on separate days. The response was assessed by both respiratory resistance (Rrs6) and transcutaneous oxygen (PTCO2). Atopic status was determined by IgE and skin prick tests. RESULTS–The results of both challenges were similar whether assessed by Rrs6 or PTCO2. There was no difference in the response to either methacholine or saline between different symptom patterns or severity grades, nor was there any correlation with either test to atopic status. CONCLUSIONS–Neither an indirect nor a direct challenge distinguished between past or present wheeze or degree of clinical severity in this group of children. Either wheezy children of this age do not have airway inflammation or bronchial responsiveness is not a marker for it.